Emotion detection through biomedical signals: A pilot study (2018)
Emotions are affective states accompanied by physiological reactions that affect cognition processes such as decision making, perception, and learning. Emotion detection can be helpful in fields like education, sports and accident prevention. In this pilot study, we used biosensors to measure heart rate and galvanic skin response of twenty-eight volunteers (fourteen male, fourteen female). They were asked to watch video clips to elicit two target emotions: Amusement and anger. The purpose of this study was to determine the relationship between mean values of biosignals and emotional states (including amusement, anger and neutral state). From the analysis of variance, Fisher least significant difference and Multiple Range test, it was observed that emotions elicited with video clips influence mean values and other features of physiological signals with a confidence level of 90%. © SPIE. Downloading of the abstract is permitted for personal use only.